The use of multimodal chromatography in the control of pharmaceutical products: new possibilities and new challenges - Otašević, Biljana; Svrkota, Bojana; Krmar, Jovana; Protić, Ana; Zečević, Mira (Archives of Pharmacy, 2022)
Liquid chromatography which implies that an analyte interacts through several separation mechanisms (modes) with a stationary phase packed in a single chromatographic column is called multimodal or mixed-mode chromatography (MMC). Based on the combined modes, MMC is seen as bimodal (RP/HILIC, RP/IEX, HILIC/IEX) or trimodal (different RP/HILIC/IEXcombinations) system. Consequently, compounds that encompass wide spectra of properties (nonpolar, polar, organic, inorganic, ionized and/or non-ionized) can be chromatographed in a single chromatographic run. The main practical achievement of this is the reduction of the number of required analyses needed per one complex sample compared to unimodal chromatographic systems. Therefore, the popularity of MMC grows rapidly in recent years together with the number of its applications. Beside common quality control issues that include active pharmaceutical ingredients and related substances analysis and impurity profiling, the range of different analytes which MMC successfully handles extends to the analyses of drugs in environmental and biological samples, peptides and proteins. Since nearly half of recently FDA approved pharmaceutical substances are in the form of a salt, the focus of MMC turned to pharmaceutical counterions analyses as well. However, separations are governed by numerous intermolecular interactions resulting from specific analyteʼs properties (size, charge, polarity) and mobile phase composition (aqueous phase ionic strength and pH value, organic solvent content) while the quality of separation can also be affected by column temperature and mobile phase flow rate. Eventually, analytical method development is challenging and demands the assistance of multifactorial optimization strategies such as the design of experiments.